2015
DOI: 10.5505/tjtes.2015.66169
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation complications encountered in forensic autopsy cases performed in XXX province.

Abstract: BACKGROUND:The purpose of this study was to determine complications of resuscitation seen during autopsies and evaluate the effectiveness of basic life support training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
(72 reference statements)
0
8
0
Order By: Relevance
“… 1 Complications caused by the inaccurate CPR performance are rib fractures, sternal fractures, pericardial and pleural haemorrhages, internal organ injuries, and pulmonary hyperdilation. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“… 1 Complications caused by the inaccurate CPR performance are rib fractures, sternal fractures, pericardial and pleural haemorrhages, internal organ injuries, and pulmonary hyperdilation. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…In at least some of those cases, pneumothorax may have been the cause of arrest rather than a result of CPR. The reported incidence of pneumothorax in humans that have undergone manual CPR is 0.6 to 3.2% (Miller et al 2014, Beydilli et al 2015, Ondruschka et al 2018. Pneumothorax can also be a complication of rib fractures with CPR in humans (Darok 2004), although it was not identified in either dog with rib fractures in this study.…”
Section: Discussionmentioning
confidence: 52%
“…Liver fractures occurred in 8.9% of cases in this study, but the reported incidence for liver fractures in human patients that have undergone conventional CPR is 0.4-2% (Meron et al 2007, Beydilli et al 2015. Based on breed, most dogs (n=9) with liver fracture had a normal or deep chest conformation, with four mixed breed dogs where conformation could not be determined, and only three barrel-chested dogs.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations